Effects of Antarctic Krill Meal in Diet on Reproductive Performance and Embryo Quality of Eriocheir sinensis - Xiaorong Huang; Ru Tan; Zhi Geng; Tao Zhang; Guangpeng Feng; Gang Yang; Feng Zhao; Ping Zhuang (Aquaculture Nutrition)
A 60-day feeding trial was conducted to evaluate the impact of dietary Antarctic krill meal on the reproductive performance and embryo quality of the Chinese mitten crab, Eriocheir sinensis. Three diets were formulated, incorporating varying levels of Antarctic krill meal at 0% (Diet K0), 10% (Diet K10), and 20% (Diet K20), with a control group fed razor clam Sinonovacula constricta. Each diet was randomly assigned to three replicate tanks, each stocked with 5 males and 10 females. Male and female weights were 145.38 ± 8.01 and 102.57 ± 9.73 g, respectively. The results revealed no significant differences in weight gain rate, specific growth rate, and survival rate. However, the hepatopancreatic weight and hepatopancreas index of female crabs in each group decreased, while gonadal weight and gonadosomatic index increased significantly after 60 days, with Diet K20 showing the highest values. Egg production and fecundity of female crabs reached their peak in Diet K20, with no significant differences in reproductive indices among all groups. The phospholipid content in Diet K20 was significantly higher than in the other groups (P<0.05). Cholesterol contents in Diet K0 and the control group were significantly higher than in Diet K10 and K20 (P<0.05). No significant differences were observed in egg diameter, egg weight, moisture, crude protein, and crude fat between the groups. The content of C20 : 2 and C20 : 4n6 was highest in Diet K0, with a significant difference compared to Diet K10 (P<0.05). However, no significant differences were found in the total content of saturated fatty acids, monounsaturated fatty acids, and polyunsaturated fatty acids among all groups. Based on the research findings, it is recommended that the optimal level of Antarctic krill meal in diets is 20%.